2011
DOI: 10.1177/0163278710397791
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of the Impact of Survey Design Characteristics on Response Rates Among Nursing Home Providers

Abstract: An experiment was conducted to maximize participation of both the Director of Nursing (DoN) and the Administrator (ADMIN) in long-term care facilities. Providers in each of the 224 randomly selected facilities were randomly assigned to 1 of 16 conditions based on the combination of data collection mode (web vs. mail), questionnaire length (short vs. long), and incentive structure. Incentive structures were determined by amount compensated if the individual completed and an additional amount per individual if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…However, Flanigan and colleagues (Flanigan, McFarlane, & Cook, 2008) have cautioned that too large of an incentive may be seen as a payment, thereby turning away many health professionals. We compensated participants $35 for participation based on findings from a prior randomized trial of survey design characteristics with a similar sample (Clark et al, 2011). When we included incentive costs with other direct costs, the average costs increased to $188 per facility for participation of at least one provider and $299 per facility for participation of both providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Flanigan and colleagues (Flanigan, McFarlane, & Cook, 2008) have cautioned that too large of an incentive may be seen as a payment, thereby turning away many health professionals. We compensated participants $35 for participation based on findings from a prior randomized trial of survey design characteristics with a similar sample (Clark et al, 2011). When we included incentive costs with other direct costs, the average costs increased to $188 per facility for participation of at least one provider and $299 per facility for participation of both providers.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection procedures were based on findings from a prior randomized trial of survey design characteristics with a similar sample (Clark et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Further details of this testing are described elsewhere (Tyler et al, 2011). Revised survey instruments and administration techniques were pilot tested and revised as needed (Clark et al, 2011).…”
Section: Nh Survey Instrumentsmentioning
confidence: 99%
“… 88 Cross-sectional surveys will be administered to eligible clinicians in paper-based format and electronically, to maximise the response rate and to minimise response bias. 88–90 Studies suggest a benchmark of 35–45% for response rates in organisational research, 89 91 and as such, a minimum response rate within these parameters will be deemed acceptable by the Labouring Together study.…”
Section: Methods and Analysismentioning
confidence: 99%
“…This is to ensure that a representative sample of clinicians is achieved to minimise selection bias, as a recent study has suggested that the mean number of contact attempts before completion of a survey per participant in healthcare research is 5.7 times. 88 Cross-sectional surveys will be administered to eligible clinicians in paper-based format and electronically, to maximise the response rate and to minimise response bias. [88][89][90] Studies suggest a benchmark of 35-45% for response rates in organisational research, 89 91 and as such, a minimum response rate within these parameters will be deemed acceptable by the Labouring Together study.…”
Section: Samplementioning
confidence: 99%